Answer to Question #20104 in Trigonometry for Kristen Woods
adding and subtracting rational expressions
(x+2)/4 + (3x+1)/3
1
2012-12-07T04:00:25-0500
Let's transform this expression using reduction to common denominator:
(x+2)/4 + (3x+1)/3 =
= (x+2)*3/(4*3) + (3x+1)*4/(3*4) =
= (3x+6)/12 + (12x+4)/12 =
= (3x+6+12x+4)/12 = (15x+10)/12.
Therefore,
(x+2)/4 + (3x+1)/3 = (15x+10)/12.
Also, we can rewrite obtained expression in the form of
(15x+10)/12 = 15x/12 + 10/12 = 5x/4 + 5/6.
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment